The future of the microprocessor business. - Bass, M.J (IEEE spectrum)
In a century in which technology left few aspects of life unchanged in some countries, the microprocessor may have been the most transformative of all. In three decades it has worked itself into our lives with a scope and depth that would have been impossible to imagine during its early development. In this paper, the authors argue that customization and speed-to-market will continue to drive the industry from the bottom up